Geoinformatics in sustainable ecosystem and society : 7th International Conference, GSES 2019, and first International Conference, GeoAI 2019, Guangzhou, China, November 21-25, 2019, Revised selected papers /: 7th International Conference, GSES 2019, and first International Conference, GeoAI 2019, Guangzhou, China, November 21-25, 2019, Revised selected papers. (2020) - Unknown
No abstract available